Tinea capitis among children at one suburban primary school in the City of Maputo, Mozambique Tinea capitis entre as crianças de uma escola primária suburbana na Cidade Maputo, Mozambique - Mohsin M. Sidat; Della Correia; Titos Paulo Buene (Revista da Sociedade Brasileira de Medicina Tropical, 2007)
This study evaluated the prevalence of Tinea capitis among schoolchildren at one primary school and also identified the causative agents. Scalp flakes were collected from children presenting clinical signs suggestive of Tinea capitis. Dermatophytes were identified by following standard mycological procedures. This study found a clinical prevalence of Tinea capitis of 9.6% (110/1149). The dermatophytes isolated were Microsporum audouinii, Trichophyton violaceum, and Trichophyton mentagrophytes. The most prevalent causative agent in this study was Microsporum audouinii, thus confirming the findings from previous cross-sectional studies carried out in the city of Maputo. O estudo avaliou a prevalência da Tinea capitis na população estudantil duma Escola Primária e também identificou os agentes causais responsáveis. Escamas do couro cabeludo foram recolhidas das crianças apresentando sinais clínicos sugestivos de Tinea capitis. Dermatófitos foram identificados seguindo procedimentos micológicos padronizados. Este estudo encontrou uma prevalência clínica de Tinea capitis de 9,6% (110/1149). Os dermatófitos isolados foram Microsporum audouinii, Trichophyton violaceum e Trichophyton mentagrophytes. O agente causal mais prevalente neste estudo foi Microsporum audouinii confirmando os achados dos estudos transversais anteriores levados a cabo na Cidade de Maputo.